2017
DOI: 10.14797/mdcj-13-2-68
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and the Heart

Abstract: Testosterone (T) is the principal male sex hormone, secreted primarily by the testes and transported in the blood by the carrier protein, sex-hormone binding globulin (SHBG). Only 1% to 2% of testosterone circulates in blood as unbound "free" testosterone, but this fraction exhibits the most potent biological activity. Dihydrotestosterone (DHT), the most biologically active androgen, is synthesized from testosterone by 5a-reductase and exerts its effects via a family of androgen receptors. Some biological effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 41 publications
0
63
0
8
Order By: Relevance
“…The most common cause of HF and impaired left ventricular dysfunction is coronary artery disease (CAD) with resulting cardiac ischemia, leading to decreased contractility and weakness of the heart muscle. It is common for men with HF to have low T levels and this leads to increased mortality [135] as they are associated with reduced heart function, loss of lean muscle mass and strength, chronic anaemia and insulin resistance [126]. Some studies have suggested that there also appears to be an inverse relationship between total and T-free levels and HF grade [69], in which case the prevalence of hypogonadism is greater than 40% [136].…”
Section: Testosterone and Heart Diseasesmentioning
confidence: 99%
“…The most common cause of HF and impaired left ventricular dysfunction is coronary artery disease (CAD) with resulting cardiac ischemia, leading to decreased contractility and weakness of the heart muscle. It is common for men with HF to have low T levels and this leads to increased mortality [135] as they are associated with reduced heart function, loss of lean muscle mass and strength, chronic anaemia and insulin resistance [126]. Some studies have suggested that there also appears to be an inverse relationship between total and T-free levels and HF grade [69], in which case the prevalence of hypogonadism is greater than 40% [136].…”
Section: Testosterone and Heart Diseasesmentioning
confidence: 99%
“…The ups-and-downs 2 of testosterone are well known because, by one hand, it presents anti-inflammatory properties as 3 it exerts an inhibitory effect on adipocyte maturation (Bianchi, 2019). However, testosterone also 4 shows a strong link with cardiovascular diseases in ageing men (Goodale et al, 2017). In the same 5 way, it has been pointed out that estradiol might have protective effects on cognition (Luine, 2014).…”
mentioning
confidence: 99%
“…This supplementary analysis is motivated due to the potential differences in how females and males 3 could react to chronic stress exposure. Briefly, and despite testosterone naturally has anti-4 inflammatory properties as it exerts an inhibitory effect on adipose tissue formation and maturation 5 (Bianchi, 2019), testosterone is also linked to greater incidence of cardiovascular diseases among 6 ageing males (Goodale et al, 2017). Equally, it has also been broadly discussed whether estradiol 7 might exert as a protective factor over cognition (Luine, 2014).…”
mentioning
confidence: 99%
“…In addition, HS‐CRP concentrations also increased, which is an inflammatory marker associated with cardiac risk, especially myocardial infarction . The cardioprotective action of androgens may be exerted by acting directly on the cardiac muscle, triggering morphological and biochemical changes in the behaviour of vascular and myocardial cells; or indirectly by increasing the cardiovascular risk markers (atherogenic lipid profile, inflammation, obesity, diabetes mellitus, and atherosclerosis) . The CLA diet showed a cardioprotective action to prevent the increase in CK, LDH, and HS‐CRP concentrations caused by testosterone deficiency, although it did not change the CK‐MB concentration.…”
Section: Discussionmentioning
confidence: 99%